Efficacy of the natural oxygen transporter HEMO2life® in cold preservation in a preclinical porcine model of donation after cardiac death. (12th April 2019) - Kaminski, Jacques; Hannaert, Patrick; Kasil, Abdelsalam; Thuillier, Raphael; Leize, Elisabeth; Delpy, Eric; Steichen, Clara; Goujon, Jean Michel; Zal, Franck; Hauet, Thierry
Summary: The growing use of marginal organs for transplantation pushes current preservation methods toward their limits, and the need for improvement is pressing. We previously demonstrated the benefits of M101, a natural extracellular oxygen carrier compatible with hypothermia, for the preservation of healthy renal grafts in a porcine model of autotransplantation. Herein, we use a variant of this preclinical model to evaluate M101 potential benefits both in static cold storage (CS) and in machine perfusion (MP) preservation in the transplantation outcomes for marginal kidneys. In the CS arm, despite the absence of obvious benefits within the first 2 weeks of follow‐up, M101 dose‐dependently improved long‐term function, normalizing creatininemia after 1 and 3 months. In the MP arm, M101 improved short‐ and long‐term functional outcomes as well as tissue integrity. Importantly, we provide evidence for the additivity of MP and M101 functional effects, showing that the addition of the compound further improves organ preservation, by reducing short‐term function loss, with no loss of function or tissue integrity recorded throughout the follow‐up. Extending previous observations with healthy kidneys, the present results point at the M101 oxygen carrier as a viable strategy to improve current organ preservation methods in marginal organ transplantation.